Transnational Social Work Practice in Thailand - Senanuch, Puchong (Asean Social Work Journal, 2023)
This study aims to investigate the problems of Thai nationals abroad, analyze transnational social work practice and propose a transnational social work practice approach drawing on documentary research and in-depth interviews. The findings indicate that 1) There is an increasing number of Thai nationals migrating to live in foreign countries and facing economic, social and cultural problems as well as being unable to access social welfare services, especially during the COVID-19 pandemic,. 2) Transnational social work practice relies on cooperation between government agencies, domestic and foreign public benefit organizations, including social workers, a process which started in 2012, when the National Social Welfare Promotion Board of Thailand determined that Thai nationals abroad are target groups that deserve social welfare services and established the Center for Promotion and Coordination for Thai Social Development Abroad, and 3) This study proposes that new knowledge and skills for social workers, as well as measures and mechanisms including social welfare services necessary for transnational social work, should be developed as part of an integrated and effective transnational social work  practice approach.